Analisis Komunikasi Interpersonal dalam Pembentukan Konsep Diri Penyintas Covid-19 - Lala Amalia; Ida Riaeni (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2022)
Interpersonal communication is one of the forms of one's self-concept. How a communication that exists can have a positive or negative influence on a person. This study aims to find out how interpersonal communication can shape the self-concept of a covid-19 survivor in the city of Cirebon. In this study, researchers used interpersonal communication theory according to De Vito (1997) which is divided into 5 namely: openness, empathy, supportive attitude, positive attitude, equality. And the theory of selfconcept according to Calhoun and Acocella (1990) which is divided into 2, namely negative self-concept and positive self-concept. The research method used in this study used descriptive qualitative research with data collection techniques using observation, interviews by providing in-depth questions, and documentation. As for the results in this study, researchers found that the influence of people around such as family, friends and neighbors in verbal and nonverbal forms has a very impact on the formation of a person's self-concept. Like the support, attention, spirit, assistance provided by people nearby the impact is very large for the formation of the self-concept of a survivor of covid 19.